Sources of Information Referred for Higher Education Institution Selection - Mohd, Noor Ismawati (Journal of Education and Vocational Research, 2014)
In response to the increase in demand on tertiary education, number of higher education institution raised dramatically over the past few decades. The scenario creates competition environment leading to the needs for understanding how students’ decision were made. Recent literature on higher education has been acknowledging the role of marketing in attracting potential students. This paper explores the decision process of selecting higher education institution within the framework of marketing communication. From the perception of students who are successfully accepted in a higher education institution, the analysis was done to investigate what was the source of information being referred. Analysis was also done to identify which source perceived by the students as their most influential source of information in deciding which institution to apply for. The finding suggests that traditional marketing tools such as news paper and magazine advertisement or publication is still effective as compared with other interactive marketing approach such as websites and education fair. The influence of their significant others such as parents, siblings and peers is also discussed.